ChemInform Abstract: Alkali Metal Bismuth(III) Chloride Double Salts. Issue 21 (6th May 2016) - Kelly, Andrew W.; Nicholas, Aaron; Ahern, John C.; Chan, Benny; Patterson, Howard H.; Pike, Robert D.
Abstract: Evaporative co‐crystallization of MCl (M: Na, K, Rb, Cs) with BiOCl in aqueous HCl and various molar ratios yields the double salts Mx Biy Cl(x+3y) ·zH2 O.